A study of offensive component compositions of most effective and used in volleyball. - Azad H.Qadir (مجلة الرافدين للعلوم الرياضية, 2007)
Important of the study : The important of this research was to discover and identify the offensive component compositions , and which is the most effective and useable during the match of volley ball Also , to know the differences between the levels of offensive component compositions. Statement of the problem : The major problem of the research was the following : - to was the following the offensive team has no ability to play with different offensive compositions in a technical performance. Aim of the study: 1-To identify on offensive component compositions of most effective and used of Iraqi varsity teams of universities in volley ball. Methodology - A sample of (60) players of Iraqi university varsity teams of 2004-2005. - A sample total of (5) from (6) university was conducted and the percentage of the sample was (83%). - A descriptive research was conducted in this study for the time of 26/2/2005 – 2/3/2005 at the college of physical education, university of salahaddin. - The researcher used standard test for the evaluator of the skill of spiking sere which has been used by international federation as an accurate instrument test : Results and Recommmmedations. On the basis of the basis of the analysis of the data, the following conclusions were presented: 1. The high and fast offensive Components of the game was most used and affective. On the other hand, the medium offensive Components of the back ward zone. 2. More emphasis on specializing and selecting players of all affective Components should be taken into consideration. 3. More emphasis on training of all kind of Components on the training unit should be taken into consideration especially on the back ward zone of the volleyball.